2016
DOI: 10.5527/wjn.v5.i1.66
|View full text |Cite
|
Sign up to set email alerts
|

Secondary amyloidosis in autoinflammatory diseases and the role of inflammation in renal damage

Abstract: The release of proinflammatory cytokines during inflammation represents an attempt to respond to injury, but it may produce detrimental effects. The inflammasome is a large, multiprotein complex that drives proinflammatory cytokine production in response to infection and tissue injury; the best-characterized inflammasome is the nod-like receptor protein-3 (NLRP3). Once activated, inflammasome leads to the active form of caspase-1, the enzyme required for the maturation of interleukin-1beta. Additional mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 46 publications
0
58
0
3
Order By: Relevance
“…It is to be considered that cardiac involvement is frequent in AL amyloidosis, but is rare in b2M amyloidosis as well as in AA amyloidosis. 34 Serum b2M levels are increased in patients with ESRD on dialysis treatment; levels in plasma typically range from 30 to 50 mg/L, much higher than the normal values (between 0.8 and 3.0 mg/L). 4 However, high plasma b2M level is not a reliable predictive marker of DRA and several patients with high plasma b2M concentration have no DRA.…”
Section: Clinical Manifestations Of Dramentioning
confidence: 99%
See 1 more Smart Citation
“…It is to be considered that cardiac involvement is frequent in AL amyloidosis, but is rare in b2M amyloidosis as well as in AA amyloidosis. 34 Serum b2M levels are increased in patients with ESRD on dialysis treatment; levels in plasma typically range from 30 to 50 mg/L, much higher than the normal values (between 0.8 and 3.0 mg/L). 4 However, high plasma b2M level is not a reliable predictive marker of DRA and several patients with high plasma b2M concentration have no DRA.…”
Section: Clinical Manifestations Of Dramentioning
confidence: 99%
“…The dialysis modality, the duration, and the frequency drive b2M clearance. 34 In fact, several studies have demonstrated that the serum levels of b2M are lower in patients treated with high-flux biocompatible membranes. 61,62 Moreover, as shown by Furuya et al, the use of high-purity dialysate with lower endotoxin level than the conventional dialysate is beneficial during HD treatment because of reduction of serum b2M, pentosidine, C-reactive protein, and IL-6 which probably accelerate amyloid deposition.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Additionally, both experimental and human studies show that the NLRP3 inflammasome plays a role in the development of acute and chronic tubulo-interstitial disease [47]. Moreover, recent data show that inflammasome activation is related to proinflammatory effects of NLRP3 in autologous nephrotoxic serum nephritis, including NLRP3-mediated glomerular release of pro-inflammatory cytokines [48]. Therefore, therapeutic blockade of the NLRP3/ASC/IL-1β axis may also be beneficial in glomerulonephritis [49].…”
Section: Discussionmentioning
confidence: 99%
“…In the largest published cohort of 374 patients with AA amyloidosis, osteomyelitis was the underlying disease for 1.3% of patients (5/374) 1. Renal dysfunction is reported to be the predominant disease manifestation with a poor functional prognosis particularly when renal dysfunction was severe at diagnosis 2. This rare but mainly irreversible complication should be discussed with patients with extended infection of large tumour prosthetic joints and who decline therapeutic strategies.…”
Section: Descriptionmentioning
confidence: 99%